From the ruins of Beirut by the reflexions on some Ray-Bans to the visionary experiences in the stereoscopic photographs by Francisco Afonso Chaves (1857-1926) - dos Reis, Victor (2016)
From a photograph (2007 World Press Photo Award) taken in the Summer of 2006 by the photojournalist Spencer Platt (1970- ) in a ruined Beirut, after Israeli bombings, the text tries, through the concept(s) of visual representation, to discuss the disintegration of the boundaries between the visible and the invisible in photographic images and to demonstrate how this disintegration leads the viewer to operate the construction of the visual. In this process he builds himself up as something more than the visual subject: a seer subject capable of visionary perceptive experiences. Divided into three parts: presence /apparition, vision/clairvoyance and image/reflection, the present essay goes back to the unknown stereoscopic photographic work of the Portuguese naturalist Francisco Afonso Chaves (1857-1926) and, in particular, to his experience regarding the fusion of different images, with the intention of comprehending how, in Portugal, these constitute one of the pioneer cases of visual extension through photography.